Using Scrum in Global Software Development: A Systematic Literature Review N. Mownika (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
This paper presents a tutorial on Kalman filtering that is designed for instruction to undergraduate students. The idea behind this work is that undergraduate students do not have much of the statistical and theoretical background necessary to fully understand the existing research papers and textbooks on this topic. Instead, this work offers an introductory experience for students which takes a more practical usage perspective on the topic, rather than the statistical derivation.  Students reading this paper should be able to understand how to apply Kalman filtering tools to mathematical problems without requiring a deep theoretical understanding of statistical theory